2017
DOI: 10.1097/qai.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on Bone Mineral Density and Bone Markers in HIV-Infected Youth

Abstract: Background Low bone mineral density (BMD) is a significant co-morbidity in HIV. However, studies evaluating vitamin D supplementation on bone health in this population are limited. This study investigates changes in bone health parameters after 12 months of supplementation in HIV-infected youth with vitamin D insufficiency. Methods This is a randomized, active-control, double-blind trial investigating changes in bone parameters with 3 different vitamin D3 doses [18,000 (standard/control dose), 60,000 (modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
1
21
1
4
Order By: Relevance
“…Influence of vitamin D on bone development in adolescents may be dose-dependent, though. In a study of HIV-infected youth, decrease in the levels of markers of bone resorption was reported only in a group receiving monthly 120 000 IU (Eckard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Influence of vitamin D on bone development in adolescents may be dose-dependent, though. In a study of HIV-infected youth, decrease in the levels of markers of bone resorption was reported only in a group receiving monthly 120 000 IU (Eckard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Few randomized, placebo-controlled trials of vitamin D supplementation have been conducted in HIV-infected children and adolescents 2428 , and only two studies to date have evaluated bone changes with supplementation 24,27 . In Eckard, et al , authors investigated changes in BMD after 12 months of supplementation in 102 HIV-infected youth 8–26 years old on ART with baseline 25(OH)D ≤30 ng/mL 27 .…”
Section: Role Of Vitamin D Deficiencymentioning
confidence: 99%
“…In Eckard, et al , authors investigated changes in BMD after 12 months of supplementation in 102 HIV-infected youth 8–26 years old on ART with baseline 25(OH)D ≤30 ng/mL 27 . In this randomized, active-control, double-blind trial, HIV-infected subjects receiving either 60,000 or 120,000 IU/month had significant increases in BMD at the LS and hip over the 12 months.…”
Section: Role Of Vitamin D Deficiencymentioning
confidence: 99%
“…To achieve a measurement >75 nmol/L, higher supplementation doses (>1,000 IU) than currently recommended were required; though it should be noted that other guidelines such as the Special Advisory Committee on Nutrition (SACN) [ 40 ], IOM [ 74 ], and European Food Safety Agency [ 75 ] guidlines are to achieve population mean levels above the threshold not intended for clinical purposes. Higher mean and trough serum 25OHD values were almost always achieved after supplementation [ 54 , 55 , 57 , 64 , 66 , 70 73 , 76 , 77 ]. Higher mean monthly 25OHD values were seen with higher doses of cholecalciferol [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Maximal physiologic PTH suppression, however, was inconsistently observed after cholecalciferol supplementation. Whilst four studies demonstrated decreased serum PTH [ 54 , 57 , 67 , 72 ], three did not, despite similar cholecalciferol dosing [ 64 , 73 , 77 ]. Decreased PTH appeared to be in part dependent on participants’ exposure to tenofovir (TDF).…”
Section: Resultsmentioning
confidence: 99%